Social conditions of smallholder dairy farmers influence their environmental decisions - Frątczak-Müller, Joanna; Rychła, Anna; Winiwarter, Wilfried; Amon, Barbara (Scientific reports, 2024)
The objective of this study is to characterize the social conditions for making agricultural decisions. Particular attention is paid to sustainable agricultural practices in dairy farming. The theoretical framework has been developed around two major explicatory perspectives: sustainable development and quality of life. In the study, we assume that the regional dimension of problems related to the sustainable development of the dairy sector requires solutions adequate to the needs of the regions to create sustainable milk production systems. We put forward a thesis on the impact of objective living conditions of farmers on the readiness to introduce changes in the farm and to apply sustainable agricultural practices. The study has been carried out using the survey method, conducted in a face-to-face interview with fifty farmers engaged in milk production. This study contributes to revealing the role of social sustainability criteria for adopting environmentally friendly farming practices. The novelty of the approach is the use of in-depth sociological analysis in research on the sustainable development of agriculture in small farms (1–5 cows). The results have revealed a significant positive relationship between the assessment of farmers’ well-being and the willingness to adopt sustainable agricultural practices. The results also suggest that the analysis of social determinants of agricultural decisions is essential for the implementation of the assumptions of sustainable agriculture. Here we demonstrate that the criteria of subjective well-being can be considered important factors in a positive attitude towards sustainable development and openness to changes in agricultural production.